Improving Students' Sustainable Environmental Awareness Using the Read-Answer-Discuss-Explain-Create Learning Model with Greenhouse Effect Animation Video: A Stacking Analysis - Sujana*, Atep; Ramadany, Lisa Dewi; Hidayat, Febrian Andi; Rachmatin, Dewi; Yunus, Sitti Rahma (Universitas Syiah Kuala, 2025)
Despite increasing global attention to environmental issues, many elementary school students still lack adequate awareness and understanding of sustainable environmental practices. This low level of awareness poses a significant challenge to achieving long-term environmental sustainability, as early education plays a critical role in shaping pro-environmental attitudes and behaviors. This study aims to examine the effect of RADEC learning model assisted by greenhouse effect animation video on improving elementary school students' sustainable environmental awareness. Using a quasi-experimental design and pretest-posttest approach, data were collected through tests measured by logit scores before and after the intervention, which included aspects of knowledge, attitudes, behaviors, and practices related to the environment. The analysis technique used was Rasch analysis with the stacking method to evaluate changes in students' environmental awareness. The results showed that the RADEC learning model with the greenhouse effect animation video successfully improved students' sustainable environmental awareness in all measured dimensions, especially in the emotional, attitudinal and behavioral, and practice dimensions. In contrast, the control class using conventional learning showed only limited improvement, with some students even experiencing a decline in ability. These findings suggest that the use of visual media and an inquiry-based approach in RADEC is more effective in improving students' environmental awareness compared to traditional learning. Therefore, this study makes an important contribution to the development of inquiry-based learning methods and visual media in sustainability education in primary schools